Computers as an environment for facilitating social interaction in children with autistic spectrum disorders - Pino, Begoña (The University of Edinburgh, 2007)
Autism is a developmental condition that affects communication, imagination and social interaction. Of these three impairments, it is the last which has the greatest negative impact on the life of children with autism and their families. Different intervention programs have attempted to address social interaction difficulties but there is clearly a need for a school-based program that helps develop social interaction and promote social skills within educationally 'natural' settings.

Teachers, parents and researchers widely believe that children with autism enjoy using computers and in most western countries, most children with autism have access to them at home or at school. Drawing from communication theory, this thesis explores the hypothesis that computers can provide a motivating, real-life environment in which social interaction in children with autism can be facilitated.

In a series of staged studies, the ways in which computers might be used to facilitate social interaction are investigated. The first phase established the level of access to computers that children with autism typically now have and how educators currently use computers with this group of children. The experience of those working in non-school based programmes aimed at developing social interaction in children with autism was also explored. It was also necessary to explore any inherent constraints on the development of software specifically aimed at children with autism.

Having established available resources and constraints, the thesis then explored the social behaviours of children with autism within a computer-based environment, using play-based activities. In a number of interlinking studies, differences and similarities in social interactions were explored when i) working on a paper-based versus computer-based version of the same two player game, ii) playing the same game at the computer, either against a partner or alone, and iii) working with a partner on a series of graded, computer-based jigsaw puzzles, with the partner acting either as a collaborator or competitor.

The findings presented illustrate the potential for eliciting increased social interaction in children with autism when working alongside other with computers, and suggest the possibility that time spent with computers by children with autism may help them to gravitate from a solitary activity towards a social one. The relevance of the findings of these studies to practice are discussed and the need for further studies highlighted.